2018
DOI: 10.1136/archdischild-2018-314907
|View full text |Cite
|
Sign up to set email alerts
|

Pulseless electrical activity: a misdiagnosed entity during asphyxia in newborn infants?

Abstract: Clinicians should be aware of the potential inaccuracy of ECG assessment during asphyxia in newborn infants and should rather rely on assessment using a combination of auscultation, palpation, pulse oximetry and ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…This cardiac electrical activity in the absence of pulse is called cardiac arrest with pulseless electrical activity, a preterminal rhythm which has been observed following severe asphyxiation. 29 In this study, bradycardia was confirmed with auscultation, and no pulseless electrical activity was encountered. Our data support that pulseless electrical activity is likely to be uncommon in neonates at delivery.…”
Section: Discussionmentioning
confidence: 52%
“…This cardiac electrical activity in the absence of pulse is called cardiac arrest with pulseless electrical activity, a preterminal rhythm which has been observed following severe asphyxiation. 29 In this study, bradycardia was confirmed with auscultation, and no pulseless electrical activity was encountered. Our data support that pulseless electrical activity is likely to be uncommon in neonates at delivery.…”
Section: Discussionmentioning
confidence: 52%
“…The study by Patel et al [6] and our clinical experience described in this report suggest that a high index of suspicion may be warranted during resuscitation of infants following severe asphyxia or other extensive perinatal insults. Integrating physical examination findings and the pulse oximeter output, specifically the absence of a pulsatile waveform, may help clinicians quickly identify PEA.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, PEA is believed to be an unusual occurrence in neonatal resuscitation, though diagnosis relies on use of ECG and a precise incidence has never been reported in this population. Recent animal data by Patel et al [6] identified PEA in nearly half of neonatal piglets following prolonged asphyxia. This finding suggests that PEA may be relatively frequent in asphyxiated newborns, such as the infant described in our case, but has been undetected prior to widespread adoption of ECG in the delivery room setting.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that PEA occurs in the delivery room [15]. Two studies report that the ECG displayed a HR during PEA in 40-50% of asphyxiated newborn piglets [48,49]. There have been one case report and a case series totaling seven cases of PEA in the delivery room during neonatal resuscitation [50][51][52][53].…”
Section: Pulseless Electrical Activitymentioning
confidence: 99%